Numerical analysis on longitudinal location optimization of vortex generator in compact heat exchangers - Gorji, M.; Mirgolbabaei, H.; Barari, A.; Domairry, G.; Nadim, Nima (2011)
In this paper, numerical, curvilinear and turbulent model has been used to investigate the effect of vortex generator's longitudinal displacement on heat transfer and fluid flow in different Reynolds numbers ranging from 500 to 3000. The numerical model has been validated with experimental results of a former study, which is resembled in a particular case. Numerical simulation shows that the vorticity enhancement would increase both Nusselt number and pressure drop. Proposed trend is not constant and the pattern in which parameters change is dependent on Reynolds number. Finally, a conjugated optimization of pressure drop and the Nusselt number has been suggested based on the order of parameter changes. © 2010 John Wiley & Sons, Ltd.